High-flame-retardant lithium ion battery multilayer diaphragm as well as preparation method and application thereof
By adopting a multi-layered lithium-ion battery separator, using materials such as polyethersulfone and SiO2 to construct gel-function coatings and ceramic or polymer coatings, the thermal stability and flame retardant performance of existing separators are solved. Problem, significantly improving the safety and flame retardant performance of the battery.
Patent Information
- Application Number
- CN202411797197.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-18
AI Technical Summary
Due to the poor electrolyte wetting and thermal stability of the existing lithium-ion battery separator materials, the battery performance and safety are degraded, making it difficult to effectively retardant and isolate combustible materials and high reactive oxygen species.
A multi-layer diaphragm structure is adopted, in which the substrate is a polyethersulfone diaphragm, and the positive electrode side is a coating composed of polymers with gel function and fast ion conductors, containing flame retardant; the negative electrode side can contain no coating or ceramics can be selected. Or polymer coating, fiber membranes are constructed by electrospinning and in-situ growth processes, and a "cover" mesh structure is formed on the SiO2 surface to enhance flame retardant properties.
The flame retardant performance and safety of lithium-ion batteries are significantly improved. By isolating combustible materials and high reactive oxygen species, the violent combustion reaction is converted into a gentle and gradual exothermic reaction, which enhances the thermal stability of the battery and the adhesion of the membrane.
Smart Images

Figure BDA0005177062500000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery diaphragm materials, and more specifically, to a highly flame-retardant lithium ion battery multilayer diaphragm and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have attracted much attention as power sources for portable electronic products, new energy vehicles, power storage devices and other products. Lithium-ion batteries are composed of four parts: positive electrode, negative electrode, separator and electrolyte. Although the separator does not directly participate in the electrochemical reaction in lithium-ion batteries, as an important component of lithium-ion batteries, its properties largely affect the performance of lithium-ion batteries. At present, polyolefins are still the most widely used and commercially successful lithium-ion battery separator materials, but due to their poor electrolyte wettability and thermal stability, the electrical performance and safety of lithium-ion batteries are reduced. Therefore, modification has become an important way to improve the performance of polyolefin separator materials and promote their application.
[0003] The existing technology mainly adopts the following measures to solve the safety problem of lithium-ion batteries: increasing internal resistance, reducing or cutting off current; flame retardancy; inhibiting lithium dendrites; material optimization, etc. Specifically:
[0004] 1) Increasing internal resistance and reducing or cutting off current, including coating a safety coating with chemical degradation between the current collector and the positive electrode and coating a safety coating PCT with high-temperature expansion function between the current collector and the positive electrode; the safety coating with chemical degradation generally includes adhesives, conductive materials and special sensitive materials to high temperature and high pressure. Special sensitive materials degrade under high temperature and high pressure, destroying the conductive network of the safety layer, blocking electronic conduction, increasing internal resistance, and even cutting off current to prevent thermal runaway, such as patent PCTCN2020106467 , PCTCN2020106471, PCTCN2020106474, etc.; Safety coating with high temperature expansion function At room temperature, the safety coating forms a good conductive network. At high temperature, the polymer matrix material expands, the conductive network is blocked, and the internal resistance increases. When a certain temperature is reached, the conductive network is almost blocked and the current is cut off, such as patents CN109167099B, CN201910731186.0, CN201910731214.9, CN201910730972.9, etc.;
[0005] 2) Flame retardant, mainly adding flame retardants to the positive and negative electrodes and the electrolyte, such as CN104835981A adding nano-resin solid flame retardant to the positive electrode, CN201980063342.9, PCTCN2019121316 adding flame retardant to the electrolyte, etc. Summary of the invention
[0006] The present invention provides a highly flame-retardant lithium-ion battery multilayer diaphragm and a preparation method and application thereof. The prepared highly flame-retardant lithium-ion battery multilayer diaphragm can isolate combustibles and highly active oxygen in a lithium-ion battery, and convert a violent combustion reaction into a mild, gradually exothermic reaction by carbonizing the combustibles in the battery.
[0007] In the first aspect, the present invention provides a highly flame-retardant multilayer diaphragm for a lithium-ion battery. The diaphragm is composed of multiple layers. A polyethersulfone diaphragm is used as a substrate. The side of the substrate close to the positive electrode is a coating composed of a polymer with a gel function and a fast ion conductor, and the polymer with a gel function contains a flame retardant; the side close to the negative electrode may not contain a coating or may select a ceramic coating or a polymer coating; the polymer coating is prepared by using cationic MOF-867-Me as a filler, blending it with polyethylene oxide and [(cyano)(4-fluorobenzenesulfonyl)]imide lithium, and by a solution casting method.
[0008] Preferably, the polyethersulfone membrane is prepared by constructing the structure of a fiber membrane by electrospinning polyethersulfone and SiO2 and performing in-situ growth processes, so that SiO2 is coated on the surface of the fiber.
[0009] Preferably, the method for preparing the polyethersulfone diaphragm comprises the following steps:
[0010] S1: Weigh polyethersulfone particles, prepare N,N-dimethylacetamide as a solvent to obtain a transparent spinning solution, prepare a polyethersulfone fiber membrane by electrospinning, spin, collect the electrospun film on aluminum foil, remove the film and dry it to obtain a polyethersulfone fiber membrane;
[0011] S2: Add SiO2 microspheres into the polyethersulfone fiber membrane, take it out after soaking, ultrasonically clean the composite fiber membrane, and dry it to obtain a polyethersulfone diaphragm.
[0012] 5. Preferably, the method for preparing the polymer coating comprises the following steps:
[0013] A1: 4-fluorobenzenesulfonyl chloride, 4-dimethylaminopyridine, 4-tert-butylcatechol and anhydrous K2CO3 are added to ultra-dry acetonitrile, and an aqueous solution of cyanamide is slowly added under an ice bath, and potassium salt is obtained by ammonolysis, and then ion exchange with anhydrous lithium perchlorate in ultra-dry acetonitrile is performed to obtain lithium (cyano)(4-fluorobenzenesulfonyl)]imide;
[0014] A2: Add anhydrous zirconium tetrachloride and HOAc to N,N-dimethylformamide to prepare solution A, add 2,2′-bipyridine-5,5′-dicarboxylic acid and triethylamine to N,N-dimethylformamide to prepare solution B, mix solutions A and B, place in an oven at 70-85°C for constant temperature reaction for 12-24 hours, dry to obtain MOF-867, disperse MOF-867 in tetrahydrofuran, add iodomethane as a methylating agent, wash with DMF and anhydrous acetone, and dry to obtain cationic MOF-867-Me;
[0015] A3: Lithium (cyano)(4-fluorophenylsulfonyl)]imide and MOF-867-Me are added to ultra-dry acetonitrile in sequence, and polyethylene oxide is added after ultrasonic treatment to form a viscous solution. The acetonitrile solvent is completely removed by vacuum drying to obtain a polymer coating.
[0016] Preferably, the flame retardant is melamine polyphosphate.
[0017] Preferably, the ceramic coating is a mica sheet coated diaphragm, and the mica sheet coated diaphragm is prepared by mixing mica sheets and lithium polyacrylate in a mass ratio of 4-9:1, stirring to obtain a mixed slurry, and then coating the slurry on a PE diaphragm.
[0018] In a second aspect, the present invention provides a method for preparing a highly flame-retardant lithium-ion battery multilayer diaphragm, comprising the following steps: consisting of a substrate, which may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, wherein the substrate adopts a polyethersulfone diaphragm, and one side of the substrate is a coating composed of a polymer with a gel function and a fast ion conductor, wherein the polymer with a gel function contains a flame retardant, and the other side may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, thereby preparing a highly flame-retardant lithium-ion battery multilayer diaphragm.
[0019] In a third aspect, the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte;
[0020] The diaphragm includes the highly flame-retardant lithium-ion battery multilayer diaphragm or the highly flame-retardant lithium-ion battery multilayer diaphragm prepared by the preparation method.
[0021] In summary, the present invention has the following beneficial effects:
[0022] 1. The metal-organic framework (MOFs) in the present invention is a kind of porous material with both organic and inorganic properties. It is not easy to agglomerate in polyethylene oxide, which can significantly enhance the strength of the electrolyte. In addition, by regulating the structure of MOFs, the interaction between MOFs and lithium salt anions can be enhanced, thereby improving the conductivity of the electrolyte.
[0023] 2. The Si-OH groups on the surface of SiO2 of the present invention undergo polycondensation and crosslinking reactions to form a Si-O-Si mesh structure layer similar to a "lid", which protects the internal diaphragm, isolates the entry of oxygen, and prevents further combustion of the flame. After the polyethersulfone diaphragm is burned by the igniter, a tiny cracking phenomenon occurs. Due to the uneven growth of SiO2 particles, the polyethersulfone diaphragm has a relatively good flame retardant effect. The polyethersulfone diaphragm has a good flame retardant effect, the size does not change during burning, and it can extinguish itself quickly after leaving the fire, thereby improving the safety of the lithium-ion battery;
[0024] 3. In the battery of the present invention, the positive electrode plate contains a flame retardant component, which cooperates with the flame retardant function of the electrolyte and the diaphragm to block the free radical chain reaction caused by the positive electrode; it is beneficial to block the rapid spread of uncontrolled.
[0025] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0027] Example
[0028] Example 1
[0029] A method for preparing a highly flame-retardant lithium-ion battery multilayer diaphragm comprises the following steps: the diaphragm is composed of a substrate, which may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, wherein the substrate is a polyethersulfone diaphragm, one side of the substrate is a coating composed of a polymer with a gel function and a fast ion conductor, wherein the polymer with a gel function contains a flame retardant, and the other side may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, thereby preparing a highly flame-retardant lithium-ion battery multilayer diaphragm.
[0030] The preparation method of the polyethersulfone diaphragm comprises the following steps:
[0031] S1: Weigh 10 g of polyethersulfone particles, prepare N,N-dimethylacetamide as a solvent to obtain a transparent spinning solution, prepare a polyethersulfone fiber membrane by electrospinning, spin, collect the electrospun film on aluminum foil, remove the film and dry it to obtain a polyethersulfone fiber membrane;
[0032] S2: Add SiO2 microspheres into the polyethersulfone fiber membrane, take it out after soaking, ultrasonically clean the composite fiber membrane, and dry it to obtain a polyethersulfone diaphragm.
[0033] The method for preparing a polymer coating comprises the following steps:
[0034] A1: 5 g 4-fluorobenzenesulfonyl chloride, 12.5 g 4-dimethylaminopyridine, 6.2 g 4-tert-butylcatechol, and 2.3 g anhydrous K2CO3 were added to 200 g ultra-dry acetonitrile, and an aqueous solution of cyanamide was slowly added under an ice bath, and potassium salt was obtained by ammonolysis, and then ion exchange with anhydrous lithium perchlorate in ultra-dry acetonitrile to obtain lithium (cyano)(4-fluorobenzenesulfonyl)]imide;
[0035] A2: 4.5 g of anhydrous zirconium tetrachloride and 20 mL of HOAc were added to N,N-dimethylformamide to prepare solution A, 5 g of 2,2′-bipyridine-5,5′-dicarboxylic acid and 3 g of triethylamine were added to N,N-dimethylformamide to prepare solution B, solutions A and B were mixed, placed in an oven at 70°C for constant temperature reaction for 24 h, and dried to obtain MOF-867, MOF-867 was dispersed in tetrahydrofuran, iodomethane was added as a methylating agent, washed with N,N-dimethylformamide and anhydrous acetone, and dried to obtain cationic MOF-867-Me;
[0036] A3: Lithium (cyano)(4-fluorophenylsulfonyl)]imide and MOF-867-Me are added to ultra-dry acetonitrile in sequence, and polyethylene oxide is added after ultrasonic treatment to form a viscous solution. The acetonitrile solvent is completely removed by vacuum drying to obtain a polymer coating.
[0037] The ceramic coating is a mica sheet coated diaphragm, and the mica sheet coated diaphragm is prepared by mixing mica sheets and lithium polyacrylate in a mass ratio of 4:1, stirring to obtain a mixed slurry, and then coating the slurry on a PE diaphragm.
[0038] Example 2
[0039] A method for preparing a highly flame-retardant lithium-ion battery multilayer diaphragm comprises the following steps: the diaphragm is composed of a substrate, which may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, wherein the substrate is a polyethersulfone diaphragm, one side of the substrate is a coating composed of a polymer with a gel function and a fast ion conductor, wherein the polymer with a gel function contains a flame retardant, and the other side may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, thereby preparing a highly flame-retardant lithium-ion battery multilayer diaphragm.
[0040] The preparation method of the polyethersulfone diaphragm comprises the following steps:
[0041] S1: Weigh 15 g of polyethersulfone particles, prepare N,N-dimethylacetamide as a solvent to obtain a transparent spinning solution, prepare a polyethersulfone fiber membrane by electrospinning, spin, collect the electrospun film on aluminum foil, remove the film and dry it to obtain a polyethersulfone fiber membrane;
[0042] S2: Add SiO2 microspheres into the polyethersulfone fiber membrane, take it out after soaking, ultrasonically clean the composite fiber membrane, and dry it to obtain a polyethersulfone diaphragm.
[0043] The method for preparing a polymer coating comprises the following steps:
[0044] A1: 8.4 g 4-fluorobenzenesulfonyl chloride, 16.1 g 4-dimethylaminopyridine, 7.2 g 4-tert-butylcatechol, and 3.6 g anhydrous K2CO3 were added to 500 g ultra-dry acetonitrile, and an aqueous solution of cyanamide was slowly added under an ice bath, and potassium salt was obtained by ammonolysis, and then ion exchange with anhydrous lithium perchlorate in ultra-dry acetonitrile to obtain lithium (cyano)(4-fluorobenzenesulfonyl)]imide;
[0045] A2: 5.2 g of anhydrous zirconium tetrachloride and 30 mL of HOAc were added to N,N-dimethylformamide to prepare solution A, 8 g of 2,2′-bipyridine-5,5′-dicarboxylic acid and 5 g of triethylamine were added to N,N-dimethylformamide to prepare solution B, solutions A and B were mixed, placed in an oven at 70°C for constant temperature reaction for 24 h, and dried to obtain MOF-867, MOF-867 was dispersed in tetrahydrofuran, iodomethane was added as a methylating agent, washed with N,N-dimethylformamide and anhydrous acetone, and dried to obtain cationic MOF-867-Me;
[0046] A3: Lithium (cyano)(4-fluorophenylsulfonyl)]imide and MOF-867-Me are added to ultra-dry acetonitrile in sequence, and polyethylene oxide is added after ultrasonic treatment to form a viscous solution. The acetonitrile solvent is completely removed by vacuum drying to obtain a polymer coating.
[0047] The ceramic coating is a mica sheet coated diaphragm, and the mica sheet coated diaphragm is prepared by mixing mica sheets and lithium polyacrylate in a mass ratio of 6:1, stirring to obtain a mixed slurry, and then coating the slurry on a PE diaphragm.
[0048] Example 3
[0049] A method for preparing a highly flame-retardant lithium-ion battery multilayer diaphragm comprises the following steps: the diaphragm is composed of a substrate, which may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, wherein the substrate is a polyethersulfone diaphragm, one side of the substrate is a coating composed of a polymer with a gel function and a fast ion conductor, wherein the polymer with a gel function contains a flame retardant, and the other side may or may not contain a coating, or may or may not contain a ceramic coating, or may or may not contain a polymer coating, thereby preparing a highly flame-retardant lithium-ion battery multilayer diaphragm.
[0050] The preparation method of the polyethersulfone diaphragm comprises the following steps:
[0051] S1: Weigh 25g of polyethersulfone particles, prepare N,N-dimethylacetamide as a solvent to obtain a transparent spinning solution, prepare a polyethersulfone fiber membrane by electrospinning, spin, collect the electrospun film on aluminum foil, remove the film and dry it to obtain a polyethersulfone fiber membrane;
[0052] S2: Add SiO2 microspheres into the polyethersulfone fiber membrane, take it out after soaking, ultrasonically clean the composite fiber membrane, and dry it to obtain a polyethersulfone diaphragm.
[0053] The method for preparing a polymer coating comprises the following steps:
[0054] A1: 15 g 4-fluorobenzenesulfonyl chloride, 10.5 g 4-dimethylaminopyridine, 3.2 g 4-tert-butylcatechol, and 5.8 g anhydrous K2CO3 were added to 200 g ultra-dry acetonitrile, and an aqueous solution of cyanamide was slowly added under an ice bath, and potassium salt was obtained by ammonolysis, and then ion exchange with anhydrous lithium perchlorate in ultra-dry acetonitrile to obtain lithium (cyano)(4-fluorobenzenesulfonyl)]imide;
[0055] A2: 6.5 g of anhydrous zirconium tetrachloride and 50 mL of HOAc were added to N,N-dimethylformamide to prepare solution A, 12 g of 2,2′-bipyridine-5,5′-dicarboxylic acid and 6 g of triethylamine were added to N,N-dimethylformamide to prepare solution B, solutions A and B were mixed, placed in an oven at 75°C for 12 h, and dried to obtain MOF-867, MOF-867 was dispersed in tetrahydrofuran, iodomethane was added as a methylating agent, washed with N,N-dimethylformamide and anhydrous acetone, and dried to obtain cationic MOF-867-Me;
[0056] A3: Lithium (cyano)(4-fluorophenylsulfonyl)]imide and MOF-867-Me are added to ultra-dry acetonitrile in sequence, and polyethylene oxide is added after ultrasonic treatment to form a viscous solution. The acetonitrile solvent is completely removed by vacuum drying to obtain a polymer coating.
[0057] The ceramic coating is a mica sheet coated diaphragm, and the mica sheet coated diaphragm is prepared by mixing mica sheets and lithium polyacrylate in a mass ratio of 9:1, stirring to obtain a mixed slurry, and then coating the slurry on a PE diaphragm.
[0058] Comparative Example
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that no polyethersulfone diaphragm is added, and the remaining steps and raw materials are the same as Example 1.
[0061] Comparative Example 2
[0062] The difference between this comparative example and Example 1 is that no polymer coating is added, and the remaining steps and raw materials are the same as Example 1.
[0063] Comparative Example 3
[0064] PP commercial diaphragm (model: Celgard 2400)
[0065] The data of the lithium ion battery separators prepared in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1.
[0066] Table 1 Performance data of multilayer lithium-ion battery separators for highly flame-retardant lithium-ion batteries
[0067]
[0068]
[0069] As shown in Table 1, compared with PP film, the air permeability of the lithium-ion battery separators in Examples 1-3 is improved within a controllable range, but the adhesion of the separators is greater than 60N, which effectively prevents the ceramic layer from falling off. At the same time, the thermal shrinkage is significantly improved, and the oxygen index is also greatly improved, which effectively improves the safety performance of the battery.
[0070] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A highly flame-retardant lithium-ion battery multilayer diaphragm, characterized in that: The diaphragm is composed of multiple layers. The substrate is a polyethersulfone diaphragm. The side of the substrate close to the positive electrode is a coating composed of a polymer with gel function and a fast ion conductor. The polymer with gel function contains a flame retardant; the side close to the negative electrode may not contain a coating or may select a ceramic coating or a polymer coating; the polymer coating is prepared by using cationic MOF-867-Me as a filler, blending it with polyethylene oxide and [(cyano)(4-fluorobenzenesulfonyl)]imide lithium, and using a solution casting method.
2. The highly flame-retardant lithium-ion battery multilayer diaphragm according to claim 1, characterized in that: The polyethersulfone membrane is prepared by constructing the structure of a fiber membrane of polyethersulfone and SiO2 through electrostatic spinning and in-situ growth processes, so that SiO2 is coated on the surface of the fiber.
3. The highly flame-retardant lithium-ion battery multilayer diaphragm according to claim 1, characterized in that: The preparation method of the polyethersulfone diaphragm comprises the following steps: S1: Weigh polyethersulfone particles, prepare N,N-dimethylacetamide as a solvent to obtain a transparent spinning solution, prepare a polyethersulfone fiber membrane by electrospinning, spin, collect the electrospun film on aluminum foil, remove the film and dry it to obtain a polyethersulfone fiber membrane; S2: Add SiO2 microspheres into the polyethersulfone fiber membrane, take it out after soaking, ultrasonically clean the composite fiber membrane, and dry it to obtain a polyethersulfone diaphragm.
4. The highly flame-retardant lithium-ion battery multilayer diaphragm according to claim 1, characterized in that: The method for preparing the polymer coating comprises the following steps: A1: 4-fluorobenzenesulfonyl chloride, 4-dimethylaminopyridine, 4-tert-butylcatechol and anhydrous K2CO3 are added to ultra-dry acetonitrile, and an aqueous solution of cyanamide is slowly added under an ice bath, and potassium salt is obtained by ammonolysis, and then ion exchange with anhydrous lithium perchlorate in ultra-dry acetonitrile is performed to obtain lithium (cyano)(4-fluorobenzenesulfonyl)]imide; A2: Add anhydrous zirconium tetrachloride and HOAc to N,N-dimethylformamide to prepare solution A, add 2,2′-bipyridine-5,5′-dicarboxylic acid and triethylamine to N,N-dimethylformamide to prepare solution B, mix solutions A and B, place in an oven at 70-85°C for constant temperature reaction for 12-24 hours, dry to obtain MOF-867, disperse MOF-867 in tetrahydrofuran, add iodomethane as a methylating agent, wash with N,N-dimethylformamide and anhydrous acetone, and dry to obtain cationic MOF-867-Me; A3: Lithium (cyano)(4-fluorophenylsulfonyl)]imide and MOF-867-Me are added to ultra-dry acetonitrile in sequence, and polyethylene oxide is added after ultrasonic treatment to form a viscous solution. The acetonitrile solvent is completely removed by vacuum drying to obtain a polymer coating.
5. The highly flame-retardant lithium-ion battery multilayer diaphragm according to claim 1, characterized in that: The flame retardant is melamine polyphosphate.
6. The highly flame-retardant lithium-ion battery multilayer diaphragm according to claim 1, characterized in that: The ceramic coating is a mica sheet coated diaphragm, and the mica sheet coated diaphragm is prepared by mixing mica sheets and lithium polyacrylate in a mass ratio of 4-9:1, stirring to obtain a mixed slurry, and then coating the slurry on a PE diaphragm.
7. The method for preparing a highly flame-retardant lithium-ion battery multilayer diaphragm according to any one of claims 1 to 6, characterized in that: The following steps are involved: The method is composed of a substrate, a coating which may or may not be present, a ceramic coating, or a polymer coating. The substrate adopts a polyethersulfone diaphragm. One side of the substrate is a coating composed of a polymer with a gel function and a fast ion conductor. The polymer with a gel function contains a flame retardant. The other side may or may not be present, or may or may not be present, thereby obtaining a highly flame-retardant lithium-ion battery multilayer diaphragm.
8. A lithium ion battery, characterized in that: Including positive electrode, negative electrode, separator and electrolyte; The diaphragm comprises the highly flame-retardant lithium-ion battery multilayer diaphragm according to any one of claims 1 to 5 or the highly flame-retardant lithium-ion battery multilayer diaphragm prepared by the preparation method according to claim 7.
Citation Information
Patent Citations
Safe lithium ion battery with anode added with nanometer resinae solid fire retardant, and manufacturing method therefor
CN104835981A
A highly safe battery and its preparation method
CN109167099B
Positive electrode and electrochemical device including the positive electrode
CN110400933B
Positive electrode and electrochemical device including the positive electrode
CN110429240B
Positive electrode sheet and electrochemical energy storage device
CN110444764A